Pooled Confirmatory Factor Analysis (PCFA) Using Structural Equation Modeling on Volunteerism Program: A Step by Step Approach - Afthanorhan, Wan Mohamad Asyraf Bin Wan; Ahmad, Sabri; Mamat, Ibrahim (International Journal of Asian Social Science, 2014)
Confirmatory Factor Analysis (CFA) has been enjoyed for most of researchers nowadays to evaluate the fitness of measurement model using structural equation modeling. In this work paper, five variables namely Motivation, Benefits, Barrier, Challenge, and Government Support will be implement in this research of volunteerism program to carry out the Confirmatory Factor Analysis (CFA). On the use of CFA will ascertain the scholar endeavours to enhance the capability of latent measurement model to be more effective and precise for drawing the conclusion besides to avoid the violate of regression assumption. Of the introduction to Cronbach Alpha, Composite Reliability, Convergent and Discriminant Validity in particular analysis are much efficient as a proof for the scholars to apply the outcome analysis for the subsequent steps. In doing so, the findings appear are more coincides of the purpose of case study. Deductively, CFA is a basis tools to provide a best fit of measurement model whereby deteriorates the error of measurement model from to be harm. The limitation of particular analysis using individual measurement is incapable to execute the CFA once consist below than four manifest variables. The introduction to pool CFA is indeed as a solution of scholars to achieve the required level of assess measurement model.